Immunization Milestones: A More Comprehensive Picture of Age-Appropriate Vaccination. (23rd May 2010) - Robison, Steve G.; Kurosky, Samantha K.; Young, Collette M.; Gallia, Charles A.; Arbor, Susan A.
Abstract : A challenge facing immunization registries is developing measures of childhood immunization coverage that contain more information for setting policy than present vaccine series up-to-date (UTD) rates. This study combined milestone analysis with provider encounter data to determine when children either do not receive indicated immunizations during medical encounters or fail to visit providers. Milestone analysis measures immunization status at key times between birth and age 2, when recommended immunizations first become late. The immunization status of a large population of children in the Oregon ALERT immunization registry and in the Oregon Health Plan was tracked across milestone ages. Findings indicate that the majority of children went back and forth with regard to having complete age-appropriate immunizations over time. We also found that immunization UTD rates when used alone are biased towards relating non-UTD status to a lack of visits to providers, instead of to provider visits on which recommended immunizations are not given.